Peran Kepuasan Pelanggan dalam Memediasi Pengaruh Kualitas Produk dan Inovasi Produk Terhadap Loyalitas Pelanggan UMKM GRS Kecamatan Bumiayu - Fikri Ansori; Sutarmin (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2026)
Business competition is currently getting tighter, business behavior always tries to maintain business amidst the competition in various ways. It can be seen from the phenomenon in MSME Guyub Rukun Saklawase (GRS) Bumiayu District, there is a decline in revenue. Further research is needed to investigate the effect of product quality and product innovation on customer loyalty mediated by customer satisfaction. This research was conducted on MSME GRS customers in Bumiayu District. The data used are primary data obtained from distributing questionnaires with a sample of 190 respondents. The sampling method used a non-probability sampling method with a purposive sampling technique. The data analysis technique in this study used the help of SmartPLS software version 4. The results of the study show: 1) product quality does not affect customer loyalty, 2) product innovation has a positive effect on customer loyalty, 3) product quality has a positive effect on customer satisfaction, 4) product innovation has a positive effect on customer satisfaction, 5) customer satisfaction has an effect on customer loyalty, 6) customer satisfaction mediates the effect of product quality on customer loyalty and 7) customer satisfaction mediates the effect of product innovation on customer loyalty.